2020
DOI: 10.1038/s41598-020-63170-w
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of immunosuppressive therapies in the treatment of IgA nephropathy: A network meta-analysis

Abstract: The protocol of this systematic review and network meta-analysis was submitted to the PROSPERO register and the registration number is CRD42019122324. The original data are available in the supplementary information. Because no human beings or animals were part of this study, ethics committee approval was not required. Search strategies. Two investigators (TJX and DLQ) independently performed a systematic literature retrieval. Commonly used databases, including Medline, Cochrane Central Register of Controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
(72 reference statements)
2
13
0
Order By: Relevance
“…The results of the present study also indicated that the downregulated IgAN-specific peptide, PPPVLAK, may function as an ACEI. Consistently, ACEI agents have been revealed to be a promising therapy for IgAN due to their significant effects on reducing proteinuria (37). Therefore, based on the results of the present study, it is proposed that absence of the pro-angiogenic peptide combined with deficiency of ACEI peptide may be involved in the pathogenesis of IgAN in pediatric patients.…”
Section: Discussionsupporting
confidence: 60%
“…The results of the present study also indicated that the downregulated IgAN-specific peptide, PPPVLAK, may function as an ACEI. Consistently, ACEI agents have been revealed to be a promising therapy for IgAN due to their significant effects on reducing proteinuria (37). Therefore, based on the results of the present study, it is proposed that absence of the pro-angiogenic peptide combined with deficiency of ACEI peptide may be involved in the pathogenesis of IgAN in pediatric patients.…”
Section: Discussionsupporting
confidence: 60%
“…The updated KDIGO guidelines suggested that all IgAN with proteinuria > 0.5 g/24 h, irrespective of whether they have hypertension, are treated with either an ACEi or ARB [ 3 ]. However, the current evidence about the different immunosuppression therapies remains to be elucidated [ 3 , 4 , 7 ]. Thus, we first conducted a retrospective cohort study with 149 IgAN patients to evaluate the effectiveness and safety of half-dose CS plus LEF vs. full-dose CS.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of immunosuppressants have been used for clinical treatment of IgAN, including cyclophosphamide (CTX), leflunomide (LEF), CS, azathioprine, mycophenolate mofetil, tacrolimus [5][6][7], etc. However, the protective role of immunosuppressive therapy was still in controversy [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the immunosuppressive therapies for IgA nephropathy, corticosteroids, cyclophosphamide, azathioprine, and mycophenolate mofetil (MMF) are the most common therapeutic agents (4). A meta-analysis (5) has systematically evaluated immunosuppressive therapy for IgA nephropathy and showed it has a significant effect on reducing renal injury caused by proliferative IgA nephropathy, but these meta-analyses focused on the short-term efficacy of immunosuppressive drugs and did not evaluate the long-term efficacy of these drugs. Another meta-analysis conducted by Natale et al (6) has reported the long-term efficacy of immunosuppressive agents but it included quasi-randomised studies and risk of bias was high, the quality of the evidence was low.…”
Section: Original Articlementioning
confidence: 99%